2014
DOI: 10.1016/j.clp.2014.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Herpes Simplex Virus in the Newborn

Abstract: Genital herpes simplex virus (HSV) infections are very common worldwide. Approximately 22% of pregnant women are infected genitally with HSV, and a majority of them are unaware of this. The most devastating consequence of maternal genital herpes is HSV disease in the newborn. Though neonatal HSV infections remain uncommon, due to the significant morbidity and mortality associated with the infection, HSV infection in the newborn is often considered in the differential diagnosis of ill neonates. The use of newer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 34 publications
(54 reference statements)
0
60
0
11
Order By: Relevance
“…Nevertheless, our study showed no significant seasonal difference in TOX‐IgM prevalence. To avoid congenital defects, it is advised that nonpregnant woman with an acute TOX infection should wait for at least 6 months before being pregnant …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our study showed no significant seasonal difference in TOX‐IgM prevalence. To avoid congenital defects, it is advised that nonpregnant woman with an acute TOX infection should wait for at least 6 months before being pregnant …”
Section: Discussionmentioning
confidence: 99%
“…1,17 The HSV cultures might not be evaluated at laboratories within all institutions, requiring specimens to be sent for outside assessment. Culture positivity is not required to initiate treatment.…”
Section: Diagnosismentioning
confidence: 99%
“…Skin eyes, and mouth disease; CNS disease; or disseminated disease may have DNAemia or viremia, resulting in positive blood HSV PCR for an extended period of time, curbing serial use as a methodology for therapeutic response. 1,11,17,[19][20][21] Laboratory assessment should take place immediately in all suspected and symptomatic neonates, in conjunction with intravenous pharmacotherapy. If a neonate is born to a mother with suspected HSV genital lesions and the neonate is asymptomatic, laboratory assessment should be obtained 24 hours after birth.…”
Section: Diagnosismentioning
confidence: 99%
“…The recent increase in genital HSV-1 incidence among women of childbearing age, particularly in developed nations, suggests that the burden of neonatal infection will continue to rise (1,5). While some infected infants exhibit only superficial infection limited to the skin, eyes, or mouth (SEM disease), about half develop invasive systemic (disseminated disease) or central nervous system (CNS disease) infections associated with significant morbidity and mortality (6,7). Currently, the antiviral medication acyclovir is the standard therapy for all forms of neonatal HSV disease.…”
Section: Introductionmentioning
confidence: 99%